Natural radioactivity in food crops and soil and estimation of the concomitant dose from tin mining areas in Nigeria - Abdu Nasiru Muhammad; Aznan Fazli Ismail; Nuraddeen Nasiru Garba (Journal of Taibah University for Science)
Mining of mineral ore is considered one of the anthropogenic sources of elevating the activity concentrations of the natural radionuclides in the environment, which in turn causes an increased risk of human exposure via the food chain. In an attempt to evaluate the radiological burdens resulting from tin mining activities in Nigeria, farm soil and sixty-two samples of different food crops grown around tin mining areas were evaluated for the activity concentrations of 226Ra, 232Th, and 40K using a high-purity germanium detector. The mean activity concentrations of 226Ra, 232Th and 40K in soil were 64.6 ± 29.5, 72.03 ± 28.73 and 680.6 ± 324.3 Bq/kg, respectively. These values were found to be higher than their corresponding world average values. However, the mean activity concentrations of the measured radionuclides in plants were below their respective world average values, as reported by UNSCEAR. The overall average annual ingestion dose due to the consumption of the analysed plants was 151 µSv/y, which is below the reported world average value of 290 µSv/y. The results obtained show that the hazard indices were low enough to cause any immediate radiological health complications due to the ingestion of the crops grown in the studied areas.